AN EXAMINATION OF SME SUSTAINABLE ECONOMIC DEVELOPMENT THROUGH GREEN ENTREPRENEURIAL AND TECHNOLOGICAL ORIENTATION AT POST COVID-19: A PRELIMINARY STUDY - Ashikul Hoque; Sandy Francis Peris; Kamisah Supian; Mohammad Waliul Hasanat (Journal of Islamic, Social, Economics and Development, 2021)
It is known that COVID-19 is considered as a pandemic for its effect on humankind. The effect of the virus is not limited to the health sector but almost every sector of society. A lot of studies have already been done on this pandemic’s effect on different sectors. From these studies, we come to know about various damages by this virus. The importance of sustainability is vital for the present condition as well as economic development. This study focuses on sustainable economic development along with information and communication technology for further action in the post-COVID 19 periods. This study went through current and previous studies on pandemic and post-pandemic situations and present a framework based on two major research questions. And a total of five hypotheses were developed from the questions. Questionnaires adapted from previous studies and select Dhaka and Chattogram of Bangladesh for sample collection. First of all a new framework was presented from two major questions supported by literature and Triple Bottom Line theory. Additionally, Reliability and validity tests were done for the questionnaire which produces a positive result. Focusing on the issue, this study recommends the SME sector for the betterment of sustainable economic development in post-COVID 19 situations for its various responsibilities and capabilities.